Electronic Word-of Mouth (E-WOM) Sentiment Analysis on Halal Certified Food Products - Ginantaka, Aditia; Masruroh, Eneng Risma Siti (Jurnal Ilmiah Pangan Halal, 2025)
Halal certification affects the buying interest that the food company in Indonesia should own. The status of halal products is characterized by including a logo on the product packaging. Analysis sentiment E-WOM (Electronic Word of Mouth) is performed to determine the community’s opinion on halal food products. Analysis of E-WOM sentiment is positive, negative or neutral. This study aimed to develop and apply the model of the pre-process measurement of sentiment analysis and determine the value of E-WOM about food products that are certified halal. The sentiment analysis method used is polarity scoring method based lexicon approach using R studio Software. In this study, the measurement of sentiment analysis can be applied to food products certified halal. The analysis of this study is negative because people are less likely to express an opinion on a few products that have been certified halal.